Strains of Xylella fastidiosa rapidly distinguished by arbitrarily primed-PCR - Costa, Paulo Inácio da [UNESP]; Franco, C. F.; Miranda, V. S.; Teixeira, D. C.; Hartung, J. S. (Springer, 2000)
Genomic DNAs isolated from strains of Xylella fastidiosa that caused citrus variegated chlorosis, coffee leaf scorch, Pierce's Disease of grapevine, and plum leaf scorch were analyzed by arbitrarily primed polymerase chain reaction. Purified DNA was amplified under nonstringent conditions with single primers 21 nucleotides (nt) long. Thirty-nine amplification products were observed that were useful to distinguish among the strains and to derive a similarity matrix and construct a phenogram showing possible relationships among the strains. Strains isolated from diseased coffee and citrus in Brazil were closely related to each other (coefficient of similarity of 0.872), but only distantly related to a strain isolated from diseased grapevine in the USA (coefficient of similarity of 0.650). Strains of Xylella fastidiosa isolated from diseased plums in the USA and Brazil clustered with strains from different hosts isolated from their respective countries of origin. Thus, there may be two quite dissimilar clusters of strains of Xylella fastidiosa, one in North America and the other in South America. Each cluster contains strains that can cause disease in plum. The methods described provide a convenient and rapid method to distinguish between strains of Xylella fastidiosa that cause diseases of coffee and citrus in the same region of Brazil. This has not been possible previously. This will potentially enable the two strains to be distinguished in alternate hosts or in insect vectors.